Appraisal of Ground Water Potential through Remote Sensing in River Basin, Pakistan - Rakhshanda Sadaf; Gohar Ali Mahar; Isma Younes (International Journal of Economic and Environmental Geology, 2018)
Groundwater is an important source of water supply throughout the world and is one of the vital parts of the hydrological cycle. Its availability depends on the precipitation and recharge conditions. In arid regions, recharge amount is smaller than semiarid regions. Recharge is the basic phenomenon for the sustainability of ground water resources. Pakistan has inadequate water resources and inflow pattern due to arid climate. There are so many factors which make the conditions gradually worst such as increasing population, change in climate condition and misuse of water resources etc. These factors lead to the situation of water scarcity rather than any addition. watershed is positioned at the boundary of Sindh and Balochistan, Pakistan. It is the most important water supply source to Industrial area and the mega city of Karachi, which is getting only about 50 percent of water supply against its fast increasing requirement. Hab watershed is therefore considered for this study. Remote Sensing and GIS are very effective tools for the assessment and exploration of potential sites of groundwater in any of the watershed. A case study was conducted for the assessment of groundwater potential sites in study area. For this purpose, different thematic layers were created like drainage map, structural and geological map and Overlay analysis was performed and to determine the potential zone of groundwater in the study area.